Analysis of the Development Direction of Small-medium Caliber Artillery - Liu, Jianbin; Zhao, Jianzhong; Lin, Lun; Zhang, Yongtao; Liu, Yan (Journal of physics. Conference series, 2023)
This paper compares the operational mechanism of artillery to laser weapon, microwave weapon and guided missile, and summarizes the advantage and inherent shortcoming of traditional gun. By carrying out the simulation of different scenarios, the hot probability of artillery to target with different characteristics at different distance is obtained. For giving full play to the advantage of artillery and improving the operational, this paper cording the development direction of artillery technology and proposes the concept of cluster artillery, provides a new idea for the leapfrog discovery of artillery technology.